Capital Flows, Financial Intermediation and Macroprudential Policies - Ghilardi, Matteo (IMF Working Papers; Working Paper ;, 2014)
This paper develops an open-economy DSGE model with an optimizing banking sector to assess the role of capital flows, macro-financial linkages, and macroprudential policies in emerging Asia. The key result is that macro-prudential measures can usefully complement monetary policy. Countercyclical macroprudential polices can help reduce macroeconomic volatility and enhance welfare. The results also demonstrate the importance of capital flows and financial stability for business cycle fluctuations as well as the role of supply side financial accelerator effects in the amplification and propagation of shocks.